Induction of Bronchial Tolerance After 1 Cycle of Monophosphoryl-A-Adjuvanted Specific Immunotherapy in Children With Grass Pollen Allergies - Rosewich, Martin (Allergy Asthma Immunol Res, 2016)
PURPOSE: Subcutaneous allergen-specific immunotherapy (SCIT) is a well-established and clinically effective method to treat allergic diseases, such as rhinitis and asthma. It remains unclear how soon after initiation of an ultra-short course of grass pollen immunotherapy adjuvanted with monophosphoryl lipid A (MPL)-specific bronchial tolerance can be induced. METHODS: In a prospective study of 69 children double-sensitized to birch and grass pollens (51 males, average age 11.1 years), development of bronchial tolerance after 1 cycle of SCIT for grass was evaluated. In all the patients, the bronchial allergen provocation test (BAP) was performed before and after treatment. According to the results of the first BAP, the patients were divided into 2 groups: those showing a negative BAP with a decrease in FEV1 of <20% (seasonal allergic rhinitis [SAR] group, n=47); and those showing a positive BAP with a decrease in FEV1 of ≥20% (SAR with allergic asthma [SAR and Asthma] group, n=22). All the patients received MPL-adjuvanted, ultra-short course immunotherapy for birch, but only those with a positive BAP to grass received MPL-SCIT for grass. RESULTS: After the pollen season, the BAP in the SAR group remained unchanged, while it was improved in the SAR and Asthma group (decrease in FEV1 of 28.8% vs 12.5%, P<0.01). The IgG4 levels increased after SCIT (median before SCIT 0.34 to 11.4 after SCIT), whereas the total and specific IgE levels remained unchanged. CONCLUSIONS: After 1 cycle of MPL-SCIT, specific bronchial tolerance may be significantly induced, whereas in patients without SCIT, bronchial hyperactivity may remain unchanged.